Safety and efficacy of stereotactic ablative brachytherapy as a salvage therapy for recurrent chest wall cancer: A retrospective, multicenter study - Huo, Bin; Ji, Zhe; He, Chuang; Yang, Wanying; Ma, Yanli; Huo, Xiaodong; Wang, Zhe; Zhao, Xinxin; Dai, Jinchao; Wang, Haitao; Chen, Guanglie; Wang, Ruoyu; et al. (Frontiers in Oncology, 2023)
Purpose To evaluate the safety and efficacy of stereotactic ablative brachytherapy (SABT) as a salvage therapy for patients with recurrent chest wall cancer (rCWC) who have previously received external beam radiotherapy (EBRT) or surgery. Materials and methods Between November 2013 and October 2020, a total of 130 patients (including 75 men with a median age of 63 years) with rCWC treated with SABT were enrolled in this multicenter retrospective study. There were 97 cases of non-small-cell lung carcinoma, 24 cases of breast cancer, and 9 cases of thymic cancer. Of the patients included, 102 patients previously received surgery and 58 patients received EBRT, with systemic treatment progressing after recurrence. None of them were suitable or refused to undergo salvage EBRT or surgery again. Results During the 22 (4–70)-month median patient follow-up, 59 patients died. The local control (LC) rates at 6, 12, 24, and 36 months were 88.3%, 74.3%, 50.4%, and 36.7%, respectively. The 1-, 2- and 3-year survival rates were 85%, 56%, and 42%, respectively. The median overall survival was 26 months (95% CI, 18.9–33.1 months). The pain relief rate was 81%, and the median to remission time was 10 days. Univariate and multivariate analyses showed that independent prognostic factors for LC included tumor size and postoperative D90. On the other hand, independent prognostic factors for survival include the Karnofsky performance status (KPS) score, tumor size, and D90 19 patients (14.6%) developed grade I/II skin reaction complications. No grade III or severer complications occurred. Conclusion SABT is safe and effective as a salvage therapy for rCWC following EBRT/surgery. For patients with a KPS score greater than 80, prescribed dose greater than 130 Gy, and tumor size less than 4 cm may bring better results.